Somatostatin immunoreactivity in quail pterygopalatine ganglion - Schrödl, Falk; De Stefano, M. Egle; Minvielle, Francis; Brehmer, Axel; Neuhuber, Winfried (Journal of Anatomy, 2005)
In the ciliary ganglion of the chicken and quail, somatostatin (SOM) is an exclusive marker for parasympathetic postganglionic neurons innervating the choroid. A second parasympathetic pathway projecting to the choroid originates from the pterygopalatine ganglion. The aim of this study was to investigate SOM immunoreactivity in the pterygopalatine ganglion of the Japanese quail (Coturnix coturnix japonica) and on neurons within the choroid, the intrinsic choroidal neurons (ICN). We did so using immunohistochemistry and subsequent light, electron and confocal laser scanning microscopy. Pterygopalatine neurons were characterized by nNOS-immunohistochemistry or NADPH-diaphorase cytochemistry. SOM immunoreactivity was absent in the perikarya, but neurons were densely surrounded by SOM-positive nerve fibres. Electron microscopy revealed that these fibres formed contacts with and without membrane specializations on pterygopalatine neurons. In the choroid, neuronal nitric-oxide synthase (nNOS)-immunoreactive ICN were likewise closely apposed by SOM-immunoreactive nerve fibres, as revealed by confocal microscopy. There was no detectable co-localization of the markers. In the absence of tracing studies, it is open to speculation whether SOM immunoreactivity originates from preganglionic fibres of the superior salivatory nucleus, postganglionic fibres of the ciliary ganglion or fibres of the brainstern via as yet unknown pathways. SOM may regulate the production of NO in pterygopalatine neurons and ICN, respectively, and is therefore involved in neuronal circuits regulating ocular homeostasis. © Anatomical Society of Great Britain and Ireland 2005.
Keywords: Autonomic innervation of the eye; Blood flow; Intrinsic choroidal neurons; NADPH-d; nNOS